Fast identification of mineral inclusions in diamond at GSECARS using synchrotron X‐ray microtomography, radiography and diffraction. (19th July 2019) - Wenz, Michelle D.; Jacobsen, Steven D.; Zhang, Dongzhou; Regier, Margo; Bausch, Hannah J.; Dera, Przemyslaw K.; Rivers, Mark; Eng, Peter; Shirey, Steven B.; Pearson, D. Graham
Abstract : Microinclusions in diamond reveal geochemical signatures from the Earth's deep mantle. A methodology is developed for non‐destructive, high‐throughput in situ characterization of mineral inclusions using synchrotron X‐ray microtomography, radiography and diffraction at GSECARS, Sector 13 of the Advanced Photon Source. Abstract : Mineral inclusions in natural diamond are widely studied for the insight that they provide into the geochemistry and dynamics of the Earth's interior. A major challenge in achieving thorough yet high rates of analysis of mineral inclusions in diamond derives from the micrometre‐scale of most inclusions, often requiring synchrotron radiation sources for diffraction. Centering microinclusions for diffraction with a highly focused synchrotron beam cannot be achieved optically because of the very high index of refraction of diamond. A fast, high‐throughput method for identification of micromineral inclusions in diamond has been developed at the GeoSoilEnviro Center for Advanced Radiation Sources (GSECARS), Advanced Photon Source, Argonne National Laboratory, USA. Diamonds and their inclusions are imaged using synchrotron 3D computed X‐ray microtomography on beamline 13‐BM‐D of GSECARS. The location of every inclusion is then pinpointed onto the coordinate system of the six‐circle goniometer of the single‐crystal diffractometer on beamline 13‐BM‐C. Because the bending magnet branch 13‐BM is divided and delivered into 13‐BM‐C and 13‐BM‐D stations simultaneously, numerous diamonds can be examined during coordinated runs. The fast, high‐throughput capability of the methodology is demonstrated by collecting 3D diffraction data on 53 diamond inclusions from Juína, Brazil, within a total of about 72 h of beam time.